Pengaruh Penggunaan Video Youtube dalam Pembelajaran Teks Prosedur: Kasus Kelas VII di SMP Negeri 1 Ngawen - Dhita Lutfi Pramesty; Fitri Yulianti; Th. Cicik Sophia B (Melati Institute, 2023)
This research used YouTube as a medium that has benefits, and the researcher used this media to research. The purpose of this research was to influence of using YouTube videos in learning procedure text. The objectives of this study are (1) to explain the students' perception of using YouTube videos in learning procedure text, (2) To explain the benefits of using YouTube videos in learning procedure text, (3) To explain the influences of using YouTube videos in learning procedure text. The researcher used a qualitative descriptive research method. The subjects were 32 students, the data by using the questionnaire and interview. The results obtained show that the score questionnaire strongly agree after being taught by YouTube was higher and from the interview data, they answered that the procedure text on YouTube was entertaining and easy to understand. it can be considered that the application YouTube media is better for students.